Gross Anatomical Studies on the Stomach of Guinea Pig (Cavia porcellus) in Postnatal Age Groups - K. Raja (Indian Journal of Veterinary Anatomy, 2022)
In the present study, stomach in guinea pigs was located in the left side of the abdominal cavity behindthe liver and diaphragm in all the postnatal age groups (n=24) i.e. from 0-2 weeks to 16-32 week-old guinea pigs.It was related to the intestine. The stomach was C shaped with smooth unilocular surface. There were twocurvatures in the stomach i.e. greater and lesser curvatures to which greater and lesser omentum were attached.Angular notch was observed on the lesser curvature of stomach in between the oesophageal opening and pyloricpart of the stomach. The internal surface of stomach of guinea pig consisted of rugae or ridges. There was nolimiting ridge observed between non glandular and glandular parts of the stomach. The size of stomach increasedwith reference to weight, volume and length in all age groups under study.